VD_FINDINFO Pron / 2011 / 116 vom 14. November 2011 - VD Tribunal cantonal (2011)
TUTELLE, PROVISOIRE, DÉCISION D'IRRECEVABILITÉ, SIGNATURE, ABSENCE, CONCLUSIONS | 17 al. 1 CPC, 380b CPC, 489 CPC, 492 CPC